Penerapan Konsultan Contract Drafting Dalam Upaya Mencegah Timbulnya Permasalahan Antara Para Pihak Yang Mengikat Dalam Perjanjian - Lau, Jonathan; Tan, David; Agustianto, Agustianto (JURNAL LEGISIA, 2025)
The development of various professions in the field of law basically plays a crucial role in supporting various legal actions such as making agreements. The existence of an agreement is crucial in underlying legal relations because it contains legal objectives that protect the parties. In line with this, this research aims to respond to the existence of the legal drafting consultant profession which has a crucial role in preventing the problem of implementing agreements. The research was conducted using normative jurisprudence method with qualitative descriptive analysis. The approach method used is statue approach and conceptual approach using primary secondary and tertiary legal materials. The results showed that the urgency of legal drafting consultants in making agreements is to help compile agreement files, carry out the legal profession credibly and responsibly, carry out the preparation of agreements independently and objectively, professionally and can protect the interests of clients. Specifically, the role of legal drafting consultants in anticipating problems arising in the agreement is to assist clients in carrying out the pre-contract stage in the form of negotiations, helping to make agreements carefully, accurately and paying careful attention to the clauses and ensuring the implementation of the agreement and anticipating disputes.